PERTANGGUNGJAWABAN PENYEDIA JASA TRANSPORTASI ONLINE TERHADAP KEAMANAN DAN KESELAMATAN KONSUMEN DITINJAU DARI UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Ranti Fauza Mayana; Aam Suryamah; Nabilah Gunawan (Faculty of Law - Tarumanagara University, 2020)
The development of globalization has a big impact on people’s lives in this era. One of them is the existence of electronic commerce (e-commerce). One e-commerce that is currently widely discussed is the online-based public transportation business, online-based public transportation has many advantages, but there are also disadvantages. Consumer safety has always been an issue for online-based public transportation companies. Because until now there are still criminal actions that result in consumers experiencing both material and immaterial losses. This paper is structured too be able to answer how to accountability is given online-based public transportation service providers to comsumers. This paper aims to provide a description of the responsibilities that must be fulfilled by service providers. The method used is normative juridical analytical descriptive research. Based on secondary data and data collection using literature studies and interviews. Based on research result, it can be seen that there are responsibilities that must be given by online-based public transportation service providers related to inadequate applications that companies create and drivers as service providers must also be accountable to consumers who suffer losses due to criminal acts that consumers experience. The form of responsibilities is compensation